RELAYOUT GUDANG BARANG JADI UNTUK MEMAKSIMALKAN KAPASITAS PRODUK JADI DENGAN MENGGUNAKAN METODE ACTIVITY RELATION CHART DAN SHARED STORAGE - Moch. Syayidi Sofyan; Atikha Sidhi Cahyana (Universitas Ahmad Dahlan Indonesia, 2017)
PT. XYZ constitute a business that move in sector of food in particular of Dry Noodle and Instan Noodle in Jl.Raya Suko KM3 Sidoarjo. In a build C of production that have three line machine of production and have one location warehouse baggage so that eventually Output from the three line machine will be saving in one warehouse the name is Finished Product Warehouse. Placement of the finished product that not organized well, make a build of production become not efficient. Layout is a main base in a industrial world. Plant layout or facilities layout can be defined as ordinances pengauran a facilities of factory to support the fluency. The purpose from this research is to give an suggestion to repair of layout about location of the finished product in a build C of production. In this research use ARC ( Activity Relation Chart ) method. ARC is an method or a simple technical in a planning of layout facility or ministry be based on the degree of relationship activities with qualitative assessment and inclined be based on opinions which is subjective from each facilities or ministry and method ( Shared Storage ). Shared storage is an method of preparation of the storage area be based on warehouse floor area condotions. As for the expected results from this research is can give an suggestion to repair of layout placement of the finished product that less ordinances well. As the result fro this research is the layout suggestion have value greater storage capacity from the initial layout with a capacity of 61 area, meanwhile for the initia capacity have value smaller as many as 44 storage area. In shared storage method the total value mileage on products A,B,C with initial layout is 142.376 m. meanwhile on suggestion of layout there are a total mileage is 94,952 m with a difference 47,424 m from distance of initial layout.Keywords: Layout, Transit Warehouse, ARC, Shared Storage